Toxic Stress and Quality of Life in Early School-Aged Ugandan Children With and Without Perinatal Human Immunodeficiency Virus Infection - Ezeamama, Amara .; Zalwango, Sarah .; Tuke, Robert; Lauren, Ricki.; Boivin, Michael .; Musoke, Philippa .; Giordani, Bruno; Sikorskii, Alla (Wiley Periodicals, Inc., 2020)
Caregiver’s and child’s self-reported quality of life (QOL) was defined using standardized questionnaires in a sample (N = 277) of 6–10 years old HIV-infected, HIV-exposed uninfected, and HIV-unexposed uninfected children from Uganda. Psychosocial stress (acute stress and cumulative lifetime adversity) and physiologic stress (dysregulations across 13 biomarkers), perinatal HIV status, and their interaction were related to child QOL via general linear models. Lower child- and caregiver-reported psychosocial stress were dose-dependently associated with higher QOL (acute stress: mean difference coefficient b = 8.1–14.8, effect size [ES] = 0.46–0.83). Lower allostasis was dose-dependently associated with higher QOL (b = 6.1–9.7, ES = 0.34–0.54). Given low caregiver acute stress, QOL for HIV-infected was similar to HIV-uninfected children; however, given high caregiver acute stress, a QOL disadvantage (b = −7.8, 95% CI: −12.8, −2.8; ES = −0.73) was evident for HIV-infected versus uninfected children.Testing of caregiver stress reduction interventions is warranted to increase wellbeing in dependent children.
Keywords: Caregiver’s; Children; quality of life; Toxic Stress; Immunodeficiency